An Entrepreneurship Research in Singapore: Basic Psychological Needs and Motivation - Sheng, Chen; Poon, Felicia (International Journal of Business, Economics and Management, 2019)
At the initial stages of starting a company, one who sets up the business and business deals is a start-up entrepreneur. This research focuses on entrepreneurs in start-up companies and explores how certain psychological needs influence motivation at the start-up stage. Basic Psychological Needs Theory is the latest and central theory from the SDT (Self-Determination Theory) (Deci and Ryan, 2000;2002). Jian et al. (2012) pointed out that psychological need is a critical factor in connecting the external environment and internal individuality. Additionally, entrepreneurial motivation is a precondition for entrepreneurship. Recent research suggests that motivation is an important role in entrepreneurial behavior and success where motivation has influenced entrepreneurs to start a business (Virginia and Carlos, 2012) . The research looks at the relationship between the psychological need and motivation of candidates of start-up in Singapore utilizing positivist approaches. Multiple regression analysis was used to analyze a causal relationship between psychological need and entrepreneurial motivation. Results found that there was a statistically significant relationship between two concepts.